Evaluation of spot urinary albumin - creatinine ratio as a screening tool in the prediction of pre-eclampsia in early pregnancy: a pilot study - G., Rajeshwari; Dongare, Akshaya Girish; Patil, G. L.; Pujar, Tejaswi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pre-eclampsia is one of the leading causes of maternal and perinatal morbidity and mortality in India. Objective of this study was to establish whether a spot urinary albumin/creatinine ratio (ACR) measured between 18-28 weeks of gestation can predict subsequent pre-eclampsia in asymptomatic pregnant women. Methods: A prospective observational study involving 50 registered antenatal cases visiting the obstetrics outpatient department between 18-28 weeks of singleton pregnancy with nil proteinuria upon dipstick measurement were included. ACR was determined from random single midstream urine sample. Statistical analysis was performed using Chi square test and Student’s t-test. Results: Of the study group, 10 patients had high ACR value, with 8(80%) developed pre-eclampsia and 2(20%) remained normotensive. ACR had a sensitivity of 80%, specificity 97.56%, positive predictive value of 88.89%, diagnostic accuracy of the test being 94.12%. Conclusions: The spot urinary protein creatinine ratio is a reliable predictor for pre-eclampsia in pregnancy.